Developing the D’Las Lembah Asri Flipbook: Integrating the CIRC Model to Improve Elementary Students’ Descriptive Writing Skills - Nirwasita, Paramesti; Purwati, Panca Dewi (Journal of Language and Literature Studies, 2026)
Elementary school students’ descriptive writing skills still face various challenges, particularly in generating, organizing, and expressing ideas coherently. Although cooperative learning models and digital media have been shown to support writing development, the integration of local wisdom into digital teaching materials remains limited. This gap highlights the need for contextual and culturally relevant instructional media to enhance students’ descriptive writing skills. This study aims to develop the D’las Lembah Asri digital flipbook based on local wisdom integrated with the Cooperative Integrated Reading and Composition (CIRC) model and to examine its feasibility and effectiveness in improving the descriptive writing skills of fourth-grade students at SDN 3 Kutabawa. The research employed a Research and Development (R&D) approach using the ADDIE model, which systematically guided the analysis, design, development, implementation, and evaluation stages of the flipbook. The results of expert validation indicated that the flipbook was categorized as highly feasible, with an average score of 91.67%. The effectiveness test demonstrated an improvement in students’ writing skills, as reflected in the increase from a pre-test average score of 62.05 to a post-test score of 77.27, with an N-gain of 0.40 (moderate category). These findings suggest that integrating local wisdom into digital learning media through the CIRC model can enhance students’ engagement and writing performance. The developed flipbook can serve as a contextual and practical digital learning resource for elementary education.